Penerapan Perlindungan Hukum Kekayaan Intelektual Atas UMKM Melalui Peogram Sabtu Minggu Di Kota Serang - Sulasno, Sulasno; Uul Nabila (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2020)
Micro, Small and Medium Enterprises (UMKM) have an important and strategic role in national economic development, UMKM in Serang City have the potential to drive the regional economy of UMKM into one of the economic pillars that drives the wheels of the economy in Indonesia. Based on data from the Serang City Industrial, Trade and Cooperatives Office, the total number in each district of the city and district of Serang reaches 10,132 UMKM, 499 MSMEs that have a small micro business license (UMK). This proves that the awareness of MSME entrepreneurs on the importance of a business permit, the importance of a brand in a product is still minimal. On this basis, we make a program called law weekend, which is a legal approach to the public or business people so that they can understand the importance of copyright, the importance of brands and contribute to trademark registration in order to protect UMKM.